Occurrence Download - Occdownload Gbif.Org (The Global Biodiversity Information Facility, 2022)
A dataset containing 468358 species occurrences available in GBIF matching the query: { "and" : [ { "or" : [ "Month is January", "Month is February", "Month is March" ] }, "TaxonKey is incertae sedis", "Year 2010-2022" ] } The dataset includes 468358 records from 873 constituent datasets: 15 records from Application INPN Espèces: Observations naturalistes, participatives et opportunistes, fondées sur des photographies. 51 records from frogid_dataset. 1 records from Jeu de données convention FEGVE-SPN-2012-2016. 3 records from Enrichment metagenome. 1 records from Données naturalistes de Damien Combrisson. 32 records from Worms (Luomus). 2 records from Canadian Museum of Nature Herbarium. 289 records from eDNA_Subseafloor. 204 records from Abyssal Baseline Study & Geophysical Survey (ABYSSLINE 02)_AB01_Re-sequenced Targeted loci environmental. 46 records from Records of protected animal, plant and fungi species in Ukraine. 26 records from Microbial ecology of archaeal community in sediment from adjacent waters of Rushan Bay. 1467 records from NOAA Deep Sea Corals Research and Technology Program. 2 records from Biodiversity monitoring in Brunswick Valley Heritage Park Mullumbimby. 94 records from marine sediment metagenome Targeted Locus (Loci). 1 records from Carnet B Centre - lot 2012. 9 records from 臺灣特有生物研究保育中心植物標本館(TAIE)苔蘚資料. 10 records from Inventaire de la flore des Pyrénées-Atlantiques 2018. 28 records from New Zealand Arthropod Collection (NZAC). 4 records from University of Vienna, Institute for Botany - Herbarium WU. 6 records from Alabama Museum of Natural History Paleontology specimens (Arctos). 7 records from Plantas Vasculares del Herbario EIF. 1 records from A_ROCHA_2017_12_18. 564 records from Sustainable Rivers Audit. 1 records from Observations naturalistes et collection entomologique en Guyane (SEAG, Julien Touroult). 371 records from Fe3+ and Mn4+ - induced changes in microbial communities of boreal lake sediments. 1 records from Porcupine Marine Natural History Society Dataset. 274 records from India Biodiversity Portal publication grade dataset. 4 records from OPIE_National_2017_12_18. 187 records from Botany (UPS). 66 records from Mississippi Entomological Museum. 102 records from Museu Paraense Emilio Goeldi Herbarium. 12 records from Effect of climate-change induced glacier melting on the benthic prokaryotic diversity in the West Antarctic Peninsula. 1 records from Herbarium specimens of Herbiers Universitaires de Clermont-Ferrand (CLF). 2 records from Detection and diversity of nitrite oxidoreductase alpha subunit (nxrA) gene of Nitrospina in the marine sediments. 22 records from MG herbarium - Museu Paraense Emílio Goeldi - Herbário Virtual REFLORA. 1 records from Inventaire de la flore des Pyrénées-Atlantiques 2017 - Littoral. 18 records from PROSERPINE_2017_12_18. 4909 records from ClimateWatch. 24 records from nhmc_ob_2019. 735 records from Puerto Rico Long-Term Coral Reef Monitoring Program Database Compilation. 286 records from Water and Sediment samples Targeted loci environmental. 105 records from HUENF herbarium - Universidade Estadual do Norte Fluminense - Herbário Virtual REFLORA. 1 records from Connaissances des sciences de la vie et de la terre en Haute-Normandie. 1 records from The Orthoptera collection (EO) of the Muséum national d'Histoire naturelle (MNHN - Paris). 3 records from Mammalia (Luomus). 3184 records from Temporal variation in pesticide biodegradation. 84 records from Sediment river Genome sequencing and assembly. 69 records from Seawater Targeted Locus (Loci). 5 records from nirS-Encoding and nirK-Encoding Denitrifiers in the Sediment of Daya Bay Raw sequence reads. 18 records from Parc_National_de_Port_Cros_2017_12_18. 7 records from Biome of Australia Soil Environments. 1 records from MPM Milwaukee Public Museum Herbarium. 296 records from Assessing the effects of salmon farming seabed enrichment using bacterial community diversity and high throughput sequencing. 266 records from Marine metagenome Targeted loci environmental. 27 records from observe_tuna_bycatch_ecoscope. 59 records from Inventaire de la flore de Dordogne 2018. 106 records from Enhanced pyrene and benzo[a]pyrene degradation by plant root and SMFC. 779 records from Diet analysis of Japanese sardine and Pacific round herring larvae. 1 records from Colección Carcinológica de Yucatán. 55 records from uncultured marine eukaryote Targeted loci environmental. 2 records from Phenology and biological traits of migrating river lamprey sampled by electrofishing in the Oir river (France).. 19 records from Naturalis Biodiversity Center (NL) - Aves. 1 records from CGMS herbarium - Universidade Federal de Mato Grosso do Sul - Herbário Virtual REFLORA. 19 records from sarce_rockyshores. 19 records from 2019_nsmk_smpl_in_800. 1 records from The cnidarians collection (IK) of the Muséum national d'Histoire naturelle (MNHN - Paris). 355 records from Microbial community in marine sediments. 31 records from Herbarium of Taiwan Forestry Research Institute. 1 records from UKSBA Cyprus - Habitat Samples, 2019. 90 records from Antarctic Snow Algae 2014/15 16S and 18S Illumina Seq of snow algae communities around Ryder Bay, Antarctica. 4 records from ZMMU MSU, White Sea Branch. 986 records from INSDC Sequences. 6 records from Données naturalistes de Damien AVRIL. 40 records from Inventaire de la flore de Dordogne 2017. 26 records from Observations du Conservatoire botanique national du Bassin parisien.. 21 records from Données photographiques validées de la galerie du forum "Le Monde des Insectes". 753 records from Santa Barbara Museum of Natural History Entomology Collection. 24 records from Hakai Institute Oceanography Program Protistan Plankton Timeseries from the Northern Salish Sea, British Columbia, Canada. 7 records from sardina_anchoveta. 39 records from 1915-2016 Department for Environment Food & Rural Affairs (Defra), Marine Strategy Framework Directive (MSFD) Collation of invasive non-indigenous species. 1 records from Wingecarribee Shire Council Macroinvertebrate Sampling. 1 records from Some finds of birds, mammals, insects, amphibians and reptiles in February 2018 in Assam, West Bengal, Bihar, Delhi and Uttar Pradesh (India). 8 records from LUSC herbarium - Universidade do Estado de Santa Catarina - Herbário Virtual Reflora. 371 records from The cryptogamy collection (PC) at the Herbarium of the Muséum national d'Histoire Naturelle (MNHN - Paris). 171 records from Groundwater microbiome. 158 records from Macaulay Library Audio and Video Collection. 21 records from Temporal dynamics of eukaryotic microbial diversity at a coastal Pacific site. 56 records from FBIP: Diversities of microbiomes from South African arid and natural soils. 855 records from Artportalen (Swedish Species Observation System). 90 records from cariaco-phytoplankton. 4 records from Observations floristiques issues de la base de données du Conservatoire botanique national alpin. 1 records from Wikiplantbase #Emilia-Romagna. 333 records from Coleoptera World (Luomus) (EC). 62 records from Depth dependent (0-5,000 m) and seasonal variability in archaeal community structure in the subarctic and subtropical western North Pacific.. 6 records from Relevé de collections de lépidoptères rhopalocères et de coléoptères saproxyliques.. 12 records from Oil-water intephase microbial community analysis Raw sequence reads. 2 records from Wikiplantbase #Toscana. 447 records from Impacts of crude oil and chemical dispersant exposure on marine microbial biofilm formation and steel corrosion. 1 records from HURB - Herbário do Recôncavo da Bahia. 40 records from MBON POLE TO POLE: SANDY BEACH BIODIVERSITY OF YUCATAN COAST. 70 records from Yarwun Port Curtis Sediment Bacterial 16S rRNA (V6) 454 sequence. 47 records from Sediment metagenome. 69 records from Dutch Foundation for Applied Water Research (STOWA) - Limnodata Neerlandica. 3 records from BioFokus. 5 records from Inventaire de la flore de Lot-et-Garonne 2018. 13 records from Shallow-water pockmarks diversity Targeted Locus (Loci). 3 records from Queensland Museum provider for OZCAM. 7 records from Herbarium Universitatis Daugavpiliensis. 1 records from Données naturalistes SLB. 1 records from International Barcode of Life project (iBOL). 1 records from EDP Foz Tua: Bat Roosts - Baseline and Complementary Studies [2008-2010]. 4 records from Lepidoptera Eastern Fennoscandia (Luomus) (LEPFEN). 4 records from Fourmis de France métropolitaine : données AntArea. 6 records from Données naturalistes d'Olivier ESCUDER. 1 records from Biodiversity Now / Nature Check (Biodiversitet Nu / NaturTjek). 30 records from disa_satyriopsis_and_associated_species. 3 records from Herbier National du Gabon. 5 records from Collection Mollusca SMF. 2 records from Inventaire de la flore de Gironde 2018. 11 records from Macrobenthos monitoring at long-term monitoring stations in the Belgian part of the North Sea from 2001 on. 1 records from Données naturalistes de Quentin ROME. 1 records from Newhaven Sanctuary observations. 3 records from Atlas des rhopalocères du Nord et du Pas-de-Calais. 12 records from Inventaire de la flore de Dordogne 2015. 932 records from SOLA Raw sequence reads. 24 records from A comparison of microbial community composition in four contrasting sediments in the Celtic Sea. 2 records from University of North Carolina at Chapel Hill Herbarium. 10 records from Données rhopalocères collectées par le CEN Aquitaine entre 1970 et 2015. 36 records from Marine Birds Observation - Total South Africa. 115 records from North Sea plastic incubation and reference communities, raw sequence reads. 101 records from Bryophyte Herbarium (H): Herbarium Generale. 4 records from DENOMBREMENT SIMULTANE ET SYNCRONISE DES OISEAUX D’EAU MIGRATEURS AU TOGO. 46 records from BRBA herbarium - Universidade Federal do Oeste da Bahia - Herbário Virtual Reflora. 38 records from Data from ILAM surveys conducted by ARCOS in Bugesera landscape for year 2016. 1 records from Données naturalistes faune du Conservatoire des espaces naturels Auvergne saisies avant le 18 février 2019.. 37 records from Sinking bloom influences benthic microorganisms. 2 records from SSNATV_2017_12_18. 2 records from Herbarium specimens of Société des Sciences Naturelles et Mathématiques de Cherbourg (CHE). 1 records from Données 2017 de l'Observatoire de la Biodiversité des Forêts. 2 records from Noosa Shire Nature Map. 3 records from AT26-10 Crab Spa IGT incubations raw sequence reads. 363 records from Données d'observation flore du réseau des CBN issues du système d'information de la FCBN. 3 records from Entomological Collections (NHRS), Swedish Museum of Natural History (NRM). 160 records from Zooplankton communities in the coastal water of northeastern Hokkaido. 2 records from The echinoderm collection (IE) of the Muséum national d'Histoire naturelle (MNHN - Paris). 22 records from Metagenetic analysis of the 18S nuclear small subunit ribosomal RNA gene of a mixed zooplankton assemblage was carried out using the 454 pyrosequencing platform.. 47 records from permafrost metagenome Targeted loci environmental. 17 records from Diversity, Ecology and Biogeochemistry of cyst-forming acantharia (Radiolaria) in the oceans. 3 records from Deposit_of_Patent_Bio-Material_in_BCRC. 1 records from Marine planktonic ciliates (phylum Ciliophora, subclasses Oligotrichia and Choreotrichia): SSU rDNA. 70 records from Melbourne Water Frog Census. 227479 records from flora&fauna(NIBR)2019. 410 records from naturgucker. 14420 records from INSDC Environment Sample Sequences. 11 records from Animal Sound Archive. 21 records from Zooplankton from selected sites in Ghana. 10 records from Availability of browse in Murchinson Falls National Park & Bugungu Wildlife Reserve. 1 records from iNaturalist Research-grade Observations. 186 records from Eucaryotic microbial communities structure in the headwater watchment of Dongjiang River in the south of China. 2 records from The crustaceans collection (IU) of the Muséum national d'Histoire naturelle (MNHN - Paris). 149 records from Comparison of marine sediments from the Beguela upwelling zone. 10 records from HUEM herbarium - Universidade Estadual de Maringá - Herbário Virtual REFLORA. 3 records from The molluscs collection (IM) of the Muséum national d'Histoire naturelle (MNHN - Paris). 174 records from Atlas of Life in the Coastal Wilderness. 2765 records from Soil marker gene sequences across the Nutrient Network. 7 records from Harvard University Herbaria: All Records. 109 records from HO AVH data. 2 records from Canadian Museum of Nature Parasite Collection. 150 records from Metagenomic approach for studying picoeukaryotes in a extreme oligotrophic marginal sea (South Adriatic Sea) during winter mixed conditions. 40 records from environmental sample sequencing. 8 records from Wikiplantbase #Sardegna. 27 records from CGMS - Herbário da Fundação Universidade Federal de Mato Grosso do Sul. 14 records from BrdU_MAB_SS Metagenome. 2 records from AMNH Bird Collection. 11 records from NEON Biorepository Terrestrial Plant Collection (Canopy Foliage). 386 records from Amplicon sequencing of Tara Oceans RNA samples corresponding to size fractions for protists.. 54 records from Observations issues des campagnes de Suivi Aérien de la Mégafaune Marine (SAMM) en 2011 et 2012. 5 records from HUEFS herbarium - Universidade Estadual de Feira de Santana - Herbário Virtual REFLORA. 9 records from University of South Carolina, A. C. Moore Herbarium. 356 records from Life in a toxic environment. 10 records from Bacterial communities from Thrombolites of Lake Sarmiento. 25 records from sea water Picoeukaryotic Community Raw sequence reads Raw sequence reads. 1 records from Martin Butterfield Mallacoota Observations. 20 records from Water reservoir’s algoflories of Fergana valleys and their comparative analysis. 50 records from Diversities of bacteria and archaea in Sanya mangrove sediments. 96 records from Aves (Luomus). 107 records from Seawater metagenome Targeted loci environmental. 24 records from University of Colorado, Museum of Natural History Herbarium Lichen Collection. 3 records from Jeux de données provenant de l'ATBI Mercantour. 1 records from Inventaire de la flore des Pyrénées-Atlantiques 2017. 40554 records from flora & fauna(NIBR). 1 records from Australian Native Plants Society, Canberra Region. 454 records from Red Sea Zooplankton Raw sequence reads. 14 records from Microbial ecology of bacteiral community in sediment from adjacent waters of Rushan Bay. 1 records from Foraminifera Metagenome. 119 records from Thermophilic endospores in temperate sediments. 14 records from CLICNAT Base de données naturaliste picarde gérée par Picardie Nature. 5 records from University of Tennessee Bryophyte Herbarium. 18 records from Research on Airborne Ice Nucleating Species. 491 records from Heterogeneity of methane seep microbiomes in the NE Pacific. 13 records from Données naturalistes de Pierre DUFRENE. 1 records from Actinomycetes Collection in BCRC. 17 records from Heliconiine Butterfly Collection Records from University of Cambridge. 159 records from South China Sea interfaces 16S amplicon sequencing. 158 records from Lajitietokeskus/FinBIF - Notebook, general observations. 213 records from Photodocumentation_of_Antarctic_Peninsula_Lichens. 13 records from Gaia Guide. 4 records from New Mexico State Collection of Arthropods. 4 records from Ecosphère_2017_12_18. 1 records from Données de FLEURY Julien (SAPROX). 5 records from University of Vermont, Pringle Herbarium. 19 records from Plant Resources Center. 28 records from Dreal Corse - Base Ogreva. 2 records from Plantas exóticas en ecosistemas de montaña de Chile – LIB-MIREN Non-native plants in mountain ecosystems of Chile – LIB-MIREN. 5 records from The DNA and Sample Repository at AIT. 11 records from Bacterial community shift in the coastal Gulf of Mexico salt-marsh sediment microcosm in vitro following exposure to the Mississippi Canyon Block 252 oil (MC252). 237 records from Sea ice and seawater Raw sequence reads. 3 records from Hétérocères de La Réunion. 857 records from Biological Impacts of Ocean Acidification. 5 records from Naturalis Biodiversity Center (NL) - Mollusca. 23 records from coastal suspended particulate matter North Sea surface Raw sequence reads. 302 records from Temperature shifts simulating secondary oil recovery. 3 records from Données faune, flore et fonge du Conservatoire des espaces naturels du Nord Pas-de-Calais. 127 records from Winter Bird Census. 5 records from Western Australian Museum provider for OZCAM. 1 records from Collection Mammalia SMF. 118 records from VIES herbarium - Universidade Federal do Espírito Santo - Herbário Virtual REFLORA. 22 records from Studies on archaeal communities from freshwater sediments based on 16S rRNA gene biomarker. 18 records from Données naturalistes de Jérôme BARBUT. 14 records from Species at 290 Leppitt Road, Upper Beaconsfield. 395 records from marine metagenome Raw sequence reads. 1 records from CEPEC herbarium - Centro de Pesquisas do Cacau - Herbário Virtual REFLORA. 30 records from Protistan plankton diversity along salt gradient. 27 records from Museu Paraense Emílio Goeldi - Ichthyology Collection. 17 records from University of Hawaii Insect Museum. 1 records from RNF - Données du Conservatoire d'espaces naturel Centre. 2 records from Species list recorded by baited cameras at deep sea area in Japan. 1512 records from LifeWatch observatory data: zooplankton observations by imaging (ZooScan) in the Belgian Part of the North Sea. 6 records from CNS AVH data. 6101 records from INSDC Host Organism Sequences. 3 records from Invertebrates Collection of the Swedish Museum of Natural History. 4 records from Auckland Museum NZ Marine Collection. 57 records from Fungal diversity in Sanya mangrove sediments, China. 132 records from BirdLife Australia, Birdata. 61 records from Lichen herbarium, UiB. 1 records from Carnet B Lorraine. 171 records from Bacterial 16S rRNA gene sequencing of Antarctic soil. 32 records from Prime Hoverfly (Insecta: Diptera: Syrphidae) Areas (PHA) as a conservation tool in Serbia. 278 records from Atlantic salmon microbiota. 19 records from ReefWatch. 1 records from Données du/de la naturaliste Bottinelli Julien provenant de la base de donnée du SINP Île-de-France CETTIA. 6 records from Bacteria Collection in BCRC. 18 records from Macrofauna collected on colonization surfaces at the East Pacific Rise 9 50 N hydrothermal vent field in 1998-2017. 407 records from North Pacific Subtropical Gyre Microbial Community. 53 records from Finnish Insect Database. 104 records from 2020_biodiversity_information_observation. 356 records from Macroalgal Morphology affects composition and settlement of microbial communities. 26 records from Spatial variation of bacterioplankton in south Atlantic Bight. 7 records from Museu Paraense Emílio Goeldi - Carcinológica Collection. 10 records from Observations occasionnelles Parc national des Pyrénées. 37 records from Herbarium Senckenbergianum (GLM) - Bryophyta. 10 records from WildNet - Queensland Wildlife Data. 6 records from Records of the Victorian Conservation Seedbank. 17 records from Bird survey of Budai salt pans in Taiwan. 3 records from MBON POLE TO POLE: ROCKY SHORE BIODIVERSITY OF ARRAIAL DO CABO - BRAZIL. 12 records from Wildlife Sightings in the City of Logan. 12 records from Mushroom Collection in BCRC. 7 records from DMNS Mammal Collection (Arctos). 7 records from Inventaire de la flore de Gironde 2016. 5 records from Observations naturalistes et collection entomologique de Julien TOUROULT. 4 records from Inventaire de la flore des Landes 2016. 666 records from Marine Water Column Samples Targeted loci environmental. 20 records from Données naturalistes de CERCOPE (Jean-Louis PRATZ). 1 records from CSIC-Real Jardín Botánico-Colección de Líquenes (MA-Lichen). 3 records from Arizona State University Hasbrouck Insect Collection. 2 records from Oskarshamn herbarium (OHN). 2 records from Données LPO Réserve naturelle nationale Marais de Müllembourg. 2 records from Michael Barkla's Observations. 10 records from BACTERIAL COMMUNITIES IN THE ACID AND THERMOPHILIC CRATER-LAKE OF THE VOLCANO "EL CHICHON", MEXICO. 29 records from Panboola Wetlands Bird Surveys. 16 records from Marine photic zone, New Caledonia Lagoon raw sequence reads, nitrogenase amplicons. 38 records from Ecological Genomics of the Eastern Tropical South Pacific Oxygen Minimum Zone Metagenome. 3 records from Données faune, flore et fonge du Conservatoire des espaces naturels de Picardie. 296 records from NHMD Entomology Collection. 6 records from Stable isotope ratios of C and N in benthic macrofauna from Mediterranean seagrass litter accumulations from Calvi Bay in 2011-2012. 2 records from Environmental Foraminifera Raw sequence reads. 1 records from UF FLMNH Ichthyology. 1 records from Suivi de l'expansion du Frelon asiatique (Vespa velutina) : données confusions autres espèces. 19 records from Comptages Wetlands, dénombrements des Oiseaux d'eau à la mi-janvier en France métropolitaine. 3 records from Projet RECOLT REcherche des COLéotpères aquatiques de Guyane – inventaire et Taxonomie. 1 records from Données naturalistes de Jean-Paul LECHAPT. 102 records from Bathing Birds - National Parks Association NSW and Birdlife Australia. 2 records from NEON Biorepository Aquatic Plant, Bryophyte, Lichen, and Macroalgae Collection (Herbarium Vouchers [Point Counts]). 7 records from Yeast Collection in BCRC. 151 records from NDFF Wall Plants Monitoring Program. 514 records from Composition and Genetic Diversity of Microbial Communities in Subtropical Coastal Wetland Sediments. 1 records from Données naturalistes de Pascal Dupont. 6 records from EAC herbarium - Universidade Federal do Ceará - Herbário Virtual REFLORA. 56 records from Marine Mammals Observations - Total South Africa. 1 records from UAZ Herpetology Collection. 2 records from Données des réserves naturelles nationales gérées par la Ligue pour la protection des oiseaux (LPO). 5 records from Records of vascular plants, bryophytes and lichens from Ukrainian Grassland Database. 1 records from Vulnerable marine ecosystems in the South Pacific Ocean region. 203 records from Bacterial Biomarkers of Marcellus Shale Activity in Pennsylvania. 3 records from Données d'invertébrés. 27 records from Inventaire de la flore des Pyrénées-Atlantiques 2016. 415 records from Microbial diversity in the Benguela coastal upwelling system as derived from 16S rRNA sequencing and RNA Stable Isotope Probing (SIP). 273 records from Relevés floristiques du protocole de l'Inventaire National Forestier de l'IGN. 1 records from water sample Raw sequence reads. 1 records from Données naturalistes de Monsieur François FOURNIER. 8 records from Inventaire de la flore des Landes 2015. 1 records from Surface sediment raw sequence reads 1. 7 records from Vertebrate fossils. 2 records from Pittsburg State University, Theodore M. Sperry Herbarium. 37 records from Great Eastern Ranges - Southern Highlands. 116 records from Environmental zooplankton Targeted Locus (Loci). 5 records from Algae (S). 622 records from Hatikka.fi observations. 1 records from Duke University Herbarium Bryophyte Collection. 5 records from Données naturalistes de Monsieur JOURDE Rémi. 7 records from Asociación Jardín Botánico La Laguna - Herbarium LAGU. 2 records from Botanical Collections of the Åbo Akademi (TUR-A). 186 records from 16S amplicons Subtropical Frontal Zone New Zealand. 6 records from The Davidson College Entomology Collection. 2 records from UEL - Coleção de Peixes - Museu de Zoologia da Universidade Estadual de Londrina. 29 records from Images and observations of mostly edible plants in Stephen Barstow’s Edible Garden in Norway, taken between 2005 and 2014. 68 records from Löydös Open Finnish Observation Database. 2 records from Mollusca (Luomus). 6 records from Diveboard - Scuba diving citizen science observations. 375 records from La Planète Revisitée, massif du Mitaraka, mission principale (février-mars 2015). 32 records from IBF Monitoring of Lichens. 44 records from Marine subseafloor sediment Targeted Locus (Loci). 3 records from UPCB herbarium - Universidade Federal de Paraná - Herbário Virtual REFLORA. 21 records from Staying cool also has consequences: increased sea ice cover disrupts food web structure in East Antarctica-Data. 3 records from Données naturalistes flore et fonge du Conservatoire des espaces naturels Auvergne saisies avant le 18 février 2019.. 3 records from RNF - Données du Conservatoire d'espaces naturel Limousin. 2145 records from Nutrient addition mesocosm experiment Targeted Locus (Loci). 825 records from Marine methane seep Targeted Locus (Loci). 92 records from Microbial community structure or iron oxyhydroxides rich mound in Satsuma Iwo-jima, Japan. 20 records from NSW AVH data. 8 records from Coleoptera Palaearctic (Luomus) (PC). 69 records from Arachnida and Myriapoda (Luomus). 103 records from HSTM herbarium - Universidade Federal do Oeste do Pará - Herbário Virtual REFLORA. 1 records from DOF - Observations from the Danish Ornithological Society. 5 records from Museu Paraense Emilio Goeldi - Annelida Collection. 4 records from SIO Benthic Invertebrate Collection. 1 records from Arkansas Natural Heritage Commission Herbarium. 1 records from Museu Paraense Emílio Goeldi - Ornithology Collection - Feathers_and_Skin. 3 records from Relevé flore vasculaire menacée de La Réunion. 128 records from Suivi Photographique des Insectes Pollinisateurs (SPIPOLL). 14 records from Kangawalla Bird Sightings. 108 records from Data from ILAM surveys conducted by ARCOS in Bugesera landscape for year 2017. 4 records from Eastern Kentucky University, Ronald L. Jones Herbarium. 54 records from Clemson University Arthropod Collection. 1 records from NEON Biorepository Carabid Collection (Pinned Vouchers). 343 records from IMOS - AusCPR: Phytoplankton Abundance. 3 records from Microbial community structures of chimney in DODO and Solitaire hydrothermal fields. 1 records from Reef fish species from Vava’u archipelago, Tonga, 2014. 382 records from Canberra Nature Map. 25 records from Waterbug Census. 5 records from Données naturalistes de MICHALKE Friedrich. 2 records from Tasmanian Museum and Art Gallery provider for OZCAM. 92 records from CEN_PACA_2017_12_18. 25 records from Shotgun Metagenome Sequencing of Lake Soyang. 1 records from CSUC Vertebrate Collection. 25 records from Bacterial community dynamics during polysaccharide degradation at contrasting sites in the Southern and Atlantic Oceans. 2 records from WIKTROP - Weed Identification and Knowledge in the Tropical and Mediterranean areas. 136 records from Liste des espèces de la faune sauvage de la base de données naturalistes Faune-France 2018.. 1330 records from Who eats the tough stuff DNA stable isotope probing (SIP) of bacteria and fungi degrading 13C-labelled lignin and cellulose in forest soils. 7 records from Banco de Datos de la Biodiversidad de la Comunitat Valenciana. 11 records from Données SAPROX - Ecole d'ingénieur de Purpan. 1 records from BODATSA: Botanical Collections. 1 records from UK Roadkill Records. 11 records from San Diego Natural History Museum Entomology Department. 1984 records from IMOS National Reference Station (NRS) - Zooplankton Abundance. 8 records from Inventaire de la flore des Pyrénées-Atlantiques 2015. 1 records from Vascular plant herbarium, UiT Tromsø Museum. 2017 records from River Murray Phytoplankton Monitoring. 1 records from Données naturalistes de FLEURY Julien. 8 records from Entomological slide collection (Luomus). 28 records from Baltic Sea high-frequency temporal study 2012 at the Linnaeus Microbial Observatory Targeted Locus (Loci). 21 records from Benthic Ocean Acidification. 10 records from Observations naturalistes de Philippe RAVAT. Inventaire entomologique du Morne Bigot. 2307 records from Raw sequence reads from soil relic DNA study. 3 records from Mulbring birds. 1 records from Naturalis Biodiversity Center (NL) - Mammalia. 3 records from CPN Metagenome. 19 records from Description of lithologic section units of IODP Hole 325-M0035A. 2 records from Observations floristiques floutées issues de la base de données flore du Conservatoire botanique national alpin. 76 records from Microbial community in permeable intertidal sediment. 15 records from Zooplankton Bongo Net Data from the 2019 and 2020 Gulf of Alaska International Year of the Salmon Expeditions. 112 records from NatureShare. 6 records from TUR Vascular plant collections of the Turku University, Herbarium generale. 1 records from Kathryn Kalmbach Herbarium. 1 records from Flora of Westgate Park - Photos from Lyn Allison. 1 records from Wolli Creek Preservation Society Bird Survey. 1 records from Inventaire de la flore du PNRLG 2016 (Gironde). 29 records from FBIP: Genetic diversity of olive insect pests and their natural enemies in the Western Cape. 6 records from Jeu de données convention Eurovia-SPN-2012-2016. 10 records from LSUMZ (LSU MNS) Fishes Collection. 2133 records from NOAA coral reef monitoring benthic data from sites across Micronesia from 2009-09-29 to 2015-09-25. 3 records from Ringing and recovery database of birds (TIPU). 2 records from Bibliographique de la faune, la flore et la fonge de France métropolitaine et outre-mer. 1 records from Ecosystem biomonitoring with eDNA: metabarcoding across the tree of life in a tropical marine environment. 1 records from UB herbarium - Universidade de Brasília - Herbário Virtual REFLORA. 44 records from Archaeal diversity of surface seawater (A3,A5,G3,G5) Targeted Locus (Loci). 7 records from Maritimes Spring Research Vessel Surveys. 2 records from NCSM Non-molluscan Invertebrates Collection. 5 records from Description of lithologic section units of IODP Hole 325-M0046A. 50 records from marine sediment metagenome Raw sequence reads. 596 records from Herbarium Senckenbergianum (FR) - Fungi. 824 records from Impact of a major inflow event on the composition and distribution of bacterioplankton communities in the Baltic Sea. 35 records from DVPR - Herbário da Universidade Tecnológica Federal do Paraná - Dois Vizinhos. 1 records from RNF - Données de la Communauté de Communes de Gevrey Chambertin. 102 records from SeaWatch-B: citizens monitoring the Belgian North Sea from the beach (2014-2018). 1 records from Hemiptera World (Luomus). 2 records from Auckland Museum Land Vertebrates Collection. 31 records from Microbial Diversity in the Southwest Atlantic Ocean and Patagonian Freshwater Bodies. 8 records from Biodiversitätsdatenbank Salzburg. 5 records from MAC herbarium - Instituto do Meio Ambiente do Estado de Alagoas - Herbário Virtual REFLORA. 2 records from Données naturalistes de Benjamin CALMONT. 52 records from Variation in freshwater stream sediment community 16S rRNA profiles along an urbanization gradient. 1 records from Minor insect orders (Luomus). 899 records from IMOS Plankton Collection - AusCPR: Zooplankton Abundance. 82 records from OBI - Robert F. Hoover Herbarium, Cal Poly State University. 2 records from Fungi (S). 2 records from Inventaire de la flore de Lot-et-Garonne 2014. 8 records from Ecological succession leads to chemosynthesis in mats colonizing wood in sea water. 1 records from University of Wyoming Dillon Lab Insect Collection. 1852 records from MARINe/PISCO: Intertidal: MARINe Long-Term Monitoring Surveys: Photo Plots and Transects Summarized. 1 records from US herbarium - Smithsonian Institute - Amostras Brasileiras Repatriadas - Herbário Virtual REFLORA. 1088 records from LifeWatch observatory data: phytoplankton observations by imaging flow cytometry (FlowCam) in the Belgian Part of the North Sea. 3 records from Wikiplantbase #Liguria. 4 records from Ichthyology Collection - Royal Ontario Museum. 46 records from Données de la base Ecosphère. 10 records from Illinois Natural History Survey Insect Collection. 1 records from Amis_des_Marais_du_Vigueirat_2017_12_18. 2 records from Inventaire de la flore de Lot-et-Garonne 2017. 1 records from Invertebrate Paleontology Division, Yale Peabody Museum. 110 records from seawater bacterial community Raw sequence reads. 1 records from Naturalis Biodiversity Center (NL) - Odonata. 1 records from Fiocruz/COLTRYP - Coleção de Trypanosoma de Mamíferos Silvestres, Domésticos e Vetores. 1 records from données naturalistes de CHAUVELIER Claude. 44 records from niek_2022. 102 records from Eukaryote diversity assessment of sediments of the Western English Channel. 49 records from marine metagenome Raw sequence reads. 7 records from UWFC Ichthyology Collection. 24 records from University of Tartu Natural History Museum and Botanical Garden DNA and Environmental Sample Collections. 3827 records from Registro de trampas cámara del monitoreo a escala de paisajes. 512 records from Marine Sediment from the Berkeley Bay Targeted Locus (Loci). 1 records from C.P. Gillette Museum of Arthropod Diversity. 2 records from Faune-Réunion - export oiseaux 28/08/2017. 51 records from Fungimap. 25 records from Data collected on citizen science web portal www.ornitho.cat. 18 records from Natural History Museum, Vienna - Herbarium W. 7 records from marine sample sequencing. 11 records from Thornlands and surrounds avifauna and herpetofauna surveys. 403 records from 16S data describing Antarctic benthic sediment. 3 records from University of Colorado, Museum of Natural History Herbarium Bryophyte Collection. 17 records from COLETA - IMAR/DOP-Uac reference collection from 1977 to 2012. 12 records from JOI Herbarium - Univille\Universidade da Região de Joinville - Herbário Virtual Reflora. 1 records from Diptera Holarctic (Luomus). 114 records from Response of soil bacteria to anthropogenic soil variables at large spatial scales. 18 records from Arizona State University Vascular Plant Herbarium. 1 records from Fungarium, Oslo (O) UiO. 3711 records from Coral-associated bacteria demonstrate phylosymbiosis and cophylogeny. 16 records from Inventaire de la flore de Lot-et-Garonne 2015. 9 records from Maritimes 4VSW Research Vessel Surveys. 5 records from Nanticoke Harbour, ON, Canada (plankton SSU 454 sequencing). 1050 records from Southern Ocean Continuous Zooplankton Recorder (SO-CPR) Survey. 802 records from Effects of Fecal Input, Environmental Conditions, and Environmental Sources on Enterococci Concentrations in an Estuarine Ecosystem. 527 records from Observations floristiques - plateforme SINP régionale SILENE PACA. 2569 records from uncultured prokaryote Targeted loci environmental. 7 records from UFRN herbarium - Universidade Federal do Rio Grande do Norte - Herbário Virtual REFLORA. 112 records from marine metagenome Raw sequence reads. 5 records from Phanerogamic Botanical Collections (S). 107 records from A study on microbial functional groups producing a climate related gas in the ocean. 2 records from ALCB herbarium - Universidade Federal da Bahia - Herbário Virtual REFLORA. 20 records from University of Tennessee at Chattanooga. 870 records from Community structure of Archaea in the western North Pacific and the Arctic Ocean. 19 records from Philippine Mollusk Symbiont - ICBG Collection. 67 records from marine sediment metagenome Targeted loci environmental. 35 records from Microbial diversity in benthic stream sediment. 10 records from BioGIS - Vascular plants - Israeli Gene Bank. 3 records from KB34 Transcriptome or Gene expression. 5 records from nifH gene in KH-11-10 and KH-13-7 cruises. 12 records from Desert Botanical Garden Herbarium. 105 records from marine metagenome Metagenome. 4 records from SA Fauna (BDBSA). 94 records from FURB herbarium - Universidade Regional de Blumenau - Herbário Virtual REFLORA. 6 records from Wikiplantbase #Italia. 2326 records from SHARK - National phytoplankton monitoring in Sweden since 1983. 58 records from NEON Biorepository Mammal Collection (DNA Extracts). 5 records from NMNH Material Samples (USNM). 72 records from Greendale Creek and Curl Curl Lagoon Bird Survey 2017 to 2019. 1 records from Système d’Information Régional sur la Faune et la Flore - FNE Centre-Val de Loire - Données saisies entre 01-01-2017 et 31-03-2018. 7 records from Inventaire de la flore des Pyrénées-Atlantiques 2014. 1 records from Accuracy of protist diversity assessments: morphology compared to cloning and direct pyrosequencing of 18S rRNA genes and ITS regions using the conspicuous tintinnid ciliates as a case study. 2 records from Données faune Indre Nature 2016-2017. 29 records from DVPR herbarium - Universidade Tecnológica Federal do Paraná - Herbário Virtual REFLORA. 1 records from Museo Historia Natural UNAH VS (MUVS) Fish Collection. 266 records from Biological rejuvenation of iron oxides in bioturbated marine sediments. 48 records from Microbial eukaryotes present in a Norwegian coastal ecosystem and in the gut content of Calanus copepods from Raunefjorden. 2 records from FBIP: Actinobacterial diversity in selected South African peatlands. 1 records from Inventaires faune. 15 records from uncultured prokaryote Metagenome. 290 records from Arctic Ocean. 43 records from DNA AVH data. 608 records from Microbial communities in estuarine sediments. 15 records from Inventaire de la flore de Lot-et-Garonne 2016. 59 records from The vascular plants collection (P) at the Herbarium of the Muséum national d'Histoire Naturelle (MNHN - Paris). 18 records from marine metagenome Targeted Locus (Loci). 10 records from bacterial community in the deep-sea surface sediments. 1909 records from SHARK - Regional monitoring, recipient control and monitoring projects of phytoplankton in Sweden since 1985. 613 records from ALA species sightings and OzAtlas. 5 records from Löydös Open Invasive Species Observations. 3 records from BCE butterfly data Spain. 576 records from Soil microbial response to organic disturbances. 1 records from Banco de Germoplasma de Especies Nativas del Instituto de Ecologia y Ambiente Humano - UNSA- Arg. 78 records from SBBG - Clifton Smith Herbarium, Santa Barbara Botanic Garden. 45 records from Non-vertebrate Paleontology, Jackson School Museum of Earth History, University of Texas at Austin. 47 records from Long term data from the Hanko Bird Observatory (Halias data). 595 records from marine sediment metagenome Targeted loci environmental. 32071 records from Marine metagenomes Metagenome. 45 records from Archaea microbial communities structure in the sediment and downarea soil of the Fengshuba Reservoir in the Guangdong Provinve, South China. 99 records from Pelagic sediment metagenome of Gulf of Kutch. 3 records from BIOGEOnet : Bryophytes occurrences in Wallonia. 5 records from Vascular Plant Herbarium: Herbarium Generale. 14 records from Pisces (Luomus). 1 records from Données naturalistes de Pierre NOEL (pnoel). 6 records from RNF - Association Loiret Nature Environnement. 1 records from UNM Earth Sciences Collection (Arctos). 742 records from SCHEMA_Sediment. 3197 records from Sediment Metagenome Raw sequence reads. 1 records from M. Andrew Johnston Research Collection. 1 records from Données de la structure Département 95 provenant de la base de donnée du SINP Île-de-France CETTIA. 92 records from Inventaire de la flore de Dordogne 2016. 4 records from Liste des espèces de la faune sauvage de la base de données naturalistes Faune-France 2017.. 83 records from Allan Herbarium (CHR). 1 records from Field Museum of Natural History (Zoology) Invertebrate Collection. 3 records from Données d'occurrence Espèces issues de la base Natura 2000 : espèces d'intérêt communautaire et autres espèces remarquables renseignées dans les FSD. 49 records from Geotraces Raw sequence reads. 2 records from Liste des oiseaux de BZM Belambo. 22 records from Museu Paraense Emílio Goeldi - Amphibia Collection. 263 records from Seasonal and spatial diversity of bacterial communities in marine sediments of Ningbo Xiangshan Coastal Ocean. 3 records from Collection Crustacea - ZSRO. 4 records from Naturalis Biodiversity Center (NL) - Cnidaria. 182 records from Eukaryotic protists Metagenome. 7 records from Herbario JA. 13 records from Biodiverskripsi: Biodiversity Theses Database. 12 records from Inventaire des Noctuelles de Guyane (Lepidoptera : Euteliidae, Erebidae, Noctuidae, Nolidae). 44 records from Impact of Plant Development on Structure and Function of Rhizosphere Microbial Community associated with Groundnut (Arachis hypogaea L.). 137 records from SA Flora (BDBSA). 9 records from Royal Botanic Garden Edinburgh Living Plant Collections (E). 57 records from Meise Botanic Garden Herbarium (BR). 7 records from Duke University Herbarium Lichen Collection. 1 records from Inventaire "Espaces Naturels Sensibles" du Plata (SORE). 1060 records from Microbial community structure is affected by cropping sequences and bio-covers under long-term no-tillage. 2 records from Australasian Virtual Herbarium (AVH) data from the State Herbarium of South Australia (AD). 157 records from The Danish Environmental Portal, species and habitats-database "Danmarks Miljøportals Naturdatabase". 11 records from Macroalgal collection of National Museum of Nature and Science (TNS). 217 records from VIES - Herbário Central da Universidade Federal do Espírito Santo. 1 records from Denver Botanic Gardens Collection of Arthropods. 8 records from Biodiversité marine de l’île de La Réunion. Programme BIOLAVE. 133 records from Fluctuating redox regimes raw sequence reads. 333 records from Lichen herbarium, Oslo (O) UiO. 2 records from parasites_deep-sea. 84 records from Loihi Seamount Targeted loci environmental. 86 records from CAS Entomology (ENT). 3 records from Museu Paraense Emílio Goeldi - Hexapoda Collection. 13 records from Metagenome analysis of picoeukaryotes from surface seawater. 8 records from Fungal atlas. 10 records from Conventions d’étude sur la biodiversité française – Partenariats du Service du patrimoine naturel. 2 records from Inventaire de la flore du Pays Bassin d'Arcachon - Val de l'Eyre 2010-2013. 50 records from SHARK - National zooplankton monitoring in Sweden since 1979. 11 records from RSA - California Botanic Garden Herbarium. 1 records from Inventaire des rhopalocères 2014. 2 records from LA - University of California, Los Angeles Herbarium. 479 records from Bacteria exposure experiment North Sea. 68 records from European Molecular Biology Laboratory Australian Mirror. 34 records from SDNHM Paleontology Collection. 2472 records from Upper Murrumbidgee Waterwatch. 5 records from MSB Mammal Collection (Arctos). 30 records from Diptera World (Luomus). 4 records from A diverse and metabolically active microbial community persists in deep subsurface clay borehole water. 5 records from solar evaporation pond sample Metagenome. 42 records from Marine sample from an Antarctic Bay Raw sequence reads. 14 records from Bhutan Biodiversity Portal data. 307 records from CEN herbarium - Embrapa Recursos Genéticos e Biotecnologia - Herbário Virtual REFLORA. 4 records from NMNH Extant Specimen Records (USNM, US). 30 records from Field Museum of Natural History (Zoology) Insect, Arachnid and Myriapod Collection. 1714 records from Extracellular DNA marine sediment Targeted Locus (Loci). 4 records from Données RNF - PNR des ballons des Vosges. 1 records from Fort Hays State University Sternberg Museum of Natural History - Vertebrate. 59 records from marine metagenome Targeted Locus (Loci). 52 records from Système d’évaluation de l’état des Eaux (SEEE) - Diatomées. 2790 records from Earth Guardians Weekly Feed. 1 records from The Albert J. Cook Arthropod Research Collection. 11 records from Parc_Naturel_Régional_du_Queyras_2017_12_18. 119 records from Reef Life Survey - Survey Records. 1 records from AlgaTerra. 145 records from LTB AVH data. 8 records from Regroupement de données Rhopalocères. 1 records from Hymenoptera World (Luomus). 116 records from Marine sediment Raw sequence reads. 58 records from Programme CARTHAM: Inventaire biologique dans le cadre de Natura 2000 en Mer. 59 records from Données acquises dans le cadre de l'activité du bureau d'étude BIOTOPE (1994 - 2013). 414 records from Birds of Northern Eurasia. 1 records from Données naturalistes d' Anne PROUZET. 92 records from Diversity of Microbial Eukaryotes in Sea Waters From Fildes Peninsula,King George Island, Antarctica. 2 records from Bacterias y Arqueas de la transición Andino-Amazónica del departamento del Caquetá - Proyecto Colombia BIO. 142 records from RB - Rio de Janeiro Botanical Garden Herbarium Collection. 37 records from Zooplancton en Bahia Magdalena, Baja California Sur, Mexico. 6 records from Collection Malakologie - SNSD. 1 records from Observations de Daniel Robin. 115 records from Arizona State University Lichen Herbarium. 17 records from Royal Dutch Angling Association (SVN) - Piscaria. 2 records from Fossils of Finland. 25 records from Sediment bacterial 16S in Hachiro polder.. 3 records from Inventaire des Coléoptères cavernicoles des Pyrénées. 31 records from Enrichment of abundant sedimentary Bathyarchaeota demonstrating organoautotrophic metabolic capabilities. 16 records from Data from ILAM surveys conducted by ARCOS in Mukura landscape for year 2016. 2 records from CRI Herbarium - Universidade do Extremo Sul Catarinense - Herbário Virtual Reflora. 1 records from University of California Santa Barbara Lichen Collection. 6 records from Herbarium specimens of Jardins botaniques and Conservatoire Botanique of Nancy (NCY). 44 records from Chandeleur Island 2016 Amplicon Study Raw sequence reads. 311 records from Microbial biogeography of 925 geothermal springs in New Zealand. 246 records from UPCB - Herbário do Departamento de Botânica. 31 records from Shotgun Metagenomic Sequencing of the Arctic Ocean during Winter-Spring Transition. 1 records from Folia Conchyliologica [2010-]. 154 records from Fishes of Texas Project (FoTX) Database - Darwin Core. 4 records from Données naturalistes de Pierre HUGUENY. 1 records from MSB Parasite Collection (Arctos). 9 records from ESA herbarium - Universidade de São Paulo - Herbário Virtual REFLORA. 38 records from CANB AVH data. 24 records from 2019_nsmk_smpl_in. 1 records from Données du/de la naturaliste Dodelin Benoît provenant de la base de donnée du SINP Île-de-France CETTIA. 1 records from Données naturalistes de ROMET Nicolas. 56 records from marine metagenome. 227 records from SAMES herbarium - Herbário São Mateus - Herbário Virtual REFLORA. 38 records from Data from ILAM surveys conducted by ARCOS in Bugesera landscape for year 2016. 1 records from Universidad del Valle de Guatemala - Herbario UVAL. 118 records from Prokaryotic microbial communities structure in the headwater watchment of Dongjiang River in the south of China. 5 records from Estonian Nature Observations Database. 1 records from UCR - University of California, Riverside Herbarium - Vascular Plants. 39 records from Prokaryotic community structure in the deep Southwest Indian Ocean with an emphasis on actinobacteria Targeted Locus (Loci). 111 records from Temporal dynamics of the particle-attached and free-living microbial communities from coastal seawater. 1 records from HCF herbarium - Universidade Tecnológica Federal do Paraná - Campus Campo Mourão - Herbário Virtual REFLORA. 3 records from Chondrichthyans Of Ireland. 27 records from Royal Botanic Garden Edinburgh Herbarium (E). 110 records from Museu_Paraense_Emilio_Goeldi_Ornithology_Collection-Skin. 374 records from Danish Mycological Society, fungal records database. 5 records from Données naturalistes de AMBEC Nils. 67 records from 16S rRNA genes Random survey. 74 records from RBINS DaRWIN. 2 records from Données naturalistes de Jean-Michel LEMAIRE. 12 records from Plant collection Natuurmuseum Brabant, Tilburg. 14 records from Benthic microbial communities in the sediments of the Southern Ocean. 349 records from The Finnish Nature League's Spring monitoring. 19 records from Inventory of Dogo-Kétou forest (South-Benin). Data mobilized in the framework of JRS Biodiversity Foundation project. 2 records from Porcupine Marine Natural History Society Records. 114 records from aquatic bacterial metagenome Raw sequence reads. 6192 records from The CPR Survey. 23 records from The Australian Zooplankton Database (1938 onwards). 7 records from BLM - National Landscape Monitoring Framework - Plants. 50 records from marine sediment metagenome Targeted loci environmental. 22 records from Uncultured Microbial Consortia in Industrialized Sites on Egypt''s Red Sea Coast Targeted loci environmental. 21 records from Eastern Mediterranean Sea Lignin and Xylan enrichments. 2 records from Colección Herbario Federico Medem Bogotá - FMB. 3 records from Global Marine biodiversity data from Seawatchers Marine Citizen Science Platform 1980-2020. 34 records from Reef Life Survey: Cryptic Fish. 1 records from Collection Herpetology SMF. 98 records from NEON Biorepository Fish Collection (DNA Extracts). 1 records from Lichen herbarium TRH, NTNU University Museum. 1 records from University of Nevada, Reno, Museum of Natural History, Entomology Research Collection. 57 records from Drinking water distribution system biofilm samples Metagenome. 7 records from Herbarium GB, University of Gothenburg. 1 records from Shropshire Ecological Data Network database. 1 records from Database for alien invasive plants occurrences in Germany. 2029 records from NIEK_NES. 9 records from Inventaire de la flore de Gironde 2014. 15 records from Lichens at Herbarium Berolinense, Berlin (B). 1 records from Données 'Flore remarquable' du Parc national des Pyrénées. 1 records from 成龍溼地鳥類生態紀錄. 33 records from Artificial stream sediment raw sequence reads. 24 records from Abundance of Rocky Reef Fishes, Invertebrates and Algae, Reef Check California (RCCA), 2006 - 2017. 90 records from Parc_National_du_Mercantour_2017_12_18. 1 records from RNF - Données de la Fédération des Réserves Catalanes. 6 records from 2019_naris_newcontents_insect. 44 records from Protists tag sequencing of 18S rRNA HV 9. 52 records from Données ONF faune-flore-fonge. 6 records from The New York Botanical Garden Herbarium (NY). 377 records from Biogeography of pelagic bacterioplankton across an antagonistic temperature-salinity gradient in the Red Sea. 7325 records from Plant niche rather than soil or species shapes the microbiota. 4 records from NOAA coral reef monitoring invertebrate data from sites across Micronesia from 2009-09-29 to 2015-09-25. 102 records from Observations naturalistes des Amis de BioObs.. 20 records from ASE herbarium - Universidade Federal de Sergipe - Herbário Virtual REFLORA. 1 records from LOB - California State University, Long Beach Herbarium. 5 records from Inventaire de la flore de Gironde 2015. 7 records from University of Tennessee Fungal Herbarium. 9 records from IMOS National Reference Stations (NRS) Phytoplankton Abundance and Biovolume. 5 records from Données acquises via le réseau du Conservatoire botanique national du Bassin parisien. 1 records from SPSF - Herbário Dom Bento José Pickel. 317 records from Brigham Young University Arthropod Museum. 15 records from Diet analysis of Pacific Bluefin Tuna larvae. 27 records from Synthèse 10x10km de la faune sauvage des Directives Oiseaux et Habitats-Faune-Flore recensée via les portails gérés par la LPO de 2013 à 2017. 6 records from Freshwater Diversity Identification for Europe (FREDIE) - funded by the German Leibniz association ( SAW-2011-ZFMK-3). 1 records from Données naturalistes de Philippe GOURDAIN. 9 records from MBON POLE TO POLE: ROCKY SHORE BIODIVERSITY OF FERNANDO DE NORONHA - BRAZIL. 7 records from Inventaire de la flore des Landes 2017. 1 records from Données sur la chasse Parc amazonien de Guyane 2010-2012. 1 records from BRI AVH data. 295 records from Effect of genetics and environment on gut bacteria in Anopheles and Aedes mosquitoes.. 1 records from University of Florida Invertebrate Paleontology. 1 records from United Herbaria of the University and ETH Zurich. 34 records from Natural History Museum (London) Collection Specimens. 7 records from NY herbarium - The New York Botanical Garden - Amostras Brasileiras Repatriadas - Herbário Virtual REFLORA. 4 records from Microbial mats and sediments from Atacama. 5 records from Collection Polychaeta SMF. 14 records from Flora Atlas N.T.. 61 records from E1 Targeted Locus (Loci). 1 records from Inventaire entomologique standardisé des ZNIEFF de Martinique, protocole utilisé de 2011 à 2013. 2064 records from anchialine metagenome Raw sequence reads. 8 records from Flore du Bassin parisien (CBNBP). 21 records from L. IS dataset. Cyanoprocaryota, Lichens, Bryophyte. 18 records from HUEMG herbarium - Universidade do Estado de Minas Gerais - Campus Carangola - Herbário Virtual REFLORA. 504 records from Lepidoptera World (Luomus) (LEPW). 1 records from University of New Hampshire - Macroalgal Collection. 17 records from Abalone seed nursing ecosystem Metagenome. 60 records from Zoologische Staatssammlung Muenchen - International Barcode of Life (iBOL) - Barcode of Life Project Specimen Data. 2 records from Museu Paraense Emilio Goeldi - Lepidoptera Collection. 92 records from FLOR - Herbário do Departamento de Botânica da Universidade Federal de Santa Catarina. 2 records from Llamara 1 evaporites metagenome. 21 records from 18S Monterey Bay Time Series: an eDNA data set from Monterey Bay, California, including years 2006, 2013 - 2016. 2 records from Coleoptera Eastern Fennoscandia (Luomus) (FC). 27 records from Patagonian fjord prokaryote community. 1 records from Archbold Biological Station Arthropod Collection. 877 records from Marine metagenomes from the bioGEOTRACES project. 1 records from UKSBA Cyprus Plant Records 2018. 8 records from HJ herbarium - Universidade Federal de Goiás - Unidade Jataí - Herbário Virtual REFLORA. 184 records from Bacteria in domestic water-storage containers with or without mosquito larvae. 55 records from Distinctive community structure and high diversity in particle-associated prokaryotes in tropical and subtropical Pacific Ocean surface seawater. 4 records from 2019_nsmk_bi_20200324. 112 records from Santa Monica Basin seep sediment incubations to assess C and N sources for F430 synthesis. 3 records from Données naturalistes de Xavier JAPIOT. 10649 records from Amplicon sequencing of Tara Oceans DNA samples corresponding to size fractions for protists.. 60 records from Microbial Biogeography and Potential Ecological Function Deep Indian Ocean Ridge. 2 records from JOI - Herbário Joinvillea. 301 records from White sea picoplankton Metagenome. 15 records from DOM nutrient stress experiment bacterial communities. 2 records from RNF - LPO Rhône-Alpes. 8 records from Marine Observations - Total South Africa. 1 records from Diptera Eastern Fennoscandia (Luomus). 23 records from Suivi Temporel des Rhopalocères de France (STERF). 5 records from soil metagenome Raw sequence reads. 7 records from All taxa records for Leicestershire and Rutland. 57 records from Parc_National_des_Ecrins_2017_12_18. 5 records from Bayside Harbour, NS, Canada (plankton SSU library 454 sequencing). 1 records from Teaching Collection. 1 records from SPF herbarium - Universidade de são Paulo - Herbário Virtual REFLORA. 1 records from ipomoea-endophytes. 2 records from Deaver Herbarium (Northern Arizona University). 82 records from uncultured marine picoeukaryote strain:Peuk_V4_NWP1 Raw sequence reads. 39 records from HUFU herbarium - Universidade Federal de Uberlândia - Herbário Virtual REFLORA. 21 records from Inventaire entomologique standardisé des ZNIEFF de Martinique, protocole utilisé en 2014 et 2015. 71 records from Microbial community in on-site tsunami sediment caused by the Great East Japan Earthquake. 83 records from Global Malaspina 2010 deep ocean expedition - rRNA pyrotags. 1 records from Samanta Orellana A. Collection. 65 records from Microbial communities in the phycosphere environment. 1 records from National fish tag database. 1 records from Verdivurdering naturmangfold E39 Stord-Os. 63 records from Indian_sediments. 1 records from CSIRO Ichthyology provider for OZCAM. 1 records from Données naturalistes de BILLI Frédéric. 4 records from VectorBase (Bioinformatics Resource for Invertebrate Vectors of Human Pathogens). 2 records from KUBI Herpetology Collection. 22 records from Tour_du_Valat_2017_12_18. 5 records from La Planète Revisitée, mission complémentaire entomologique, massif du Mitaraka, août 2015. 3 records from University of Hargeisa Herbarium. 2 records from Fungi Collection in BCRC. 12 records from Biometric measurements of the seagrass Zostera noltii in the Mira channel of the Ria de Aveiro throughout the year 2020. 1 records from Données naturalistes de Bernard Lalanne-Cassou. 75 records from FLOR herbarium - Universidade Federal de Santa Catarina - Herbário Virtual REFLORA. 21 records from ArtenFinder. 3 records from Amphibia and Reptilia (Luomus). 1 records from Monitoring of the effects of Belgian wind mill parks on benthic macro-invertebrates and the fish fauna of soft substrates - reference situation. (WINMON). 1 records from PlantBank Records. 1 records from Naturalis Biodiversity Center (NL) - Porifera. 10 records from RNF - Données de l'association Vivarmor Nature. 41 records from Marine plankton Metagenome. 6 records from Prospecting of extreme microbial ecosystems associated to minerals (microbialites, microbial mats and endoevaporites) in Puna, Wetlands and Salars of Argentina, Chile and Bolivia. 130 records from Enrichment of abundant sedimentary Bathyarchaeota demonstrating organoautotrophic metabolic capabilities. 33 records from Microbial diversity of marine sediments from Ross Sea. 1 records from UKSBA Cyprus - Quadrats 2015-2017. 2 records from Inventaire de la flore des Landes 2018. 75 records from marine sediment metagenome Raw sequence reads. 126 records from Bacterial diversity in the South Adriatic Sea during winter of 2016. 55 records from Bacterial communities in agricultural soils under contrasting agronomic managements and biomes of Argentina. 15 records from Données naturalistes de Thomas GAILLARD. 10 records from seawater metagenome Metagenome. 3 records from Fauna Atlas N.T.. 13 records from Invertebrata varia (Luomus). 35 records from Frost Entomological Museum. 1 records from Données opportunistes. 1 records from Auburn University Museum of Natural History Mollusks. 1438 records from NSW Waterwatch. 4 records from Yoann_BLANCHON_2017_12_18. 1 records from UNIP herbarium - Universidade Paulista - Herbário Virtual Reflora. 2 records from Données de la flore d’Alsace (SBA). 1 records from Alain_SADORGE_2017_12_18. 9 records from LUSC - Herbário de Lages da Universidade do Estado de Santa Catarina. 1 records from History of Life Exhibition. 6 records from Diptera Collection - Instituto Nacional de Pesquisas da Amazônia (INPA). 92 records from atmospheric depositon effect on bacterial diversity. 10 records from marine metagenome. 250 records from Système d’évaluation de l’état des Eaux (SEEE) - Invertébrés. 51 records from Microbial community response on waste water discharge in recipient freshwater sediments. 2 records from Bénédicte_CULORIER_2017_12_18. 33 records from 1)sediments; 2) coral floc Metagenome. 51 records from Australian Museum provider for OZCAM. 39 records from Seawater free living bacterioplankton. 9 records from Cave sediment Metagenome. 478 records from Depth profile of ancient sediments. 119 records from Marine Biological Sample Database, JAMSTEC. 3 records from Characterization of bacterial communities associated With toxic Dinoflagellates: pyrodinium bahamense Var. compressum. 192 records from Observation.org, Nature data from around the World. 45 records from MBM herbarium - Museu Botânico Municipal \ Curitiba - Herbário Virtual REFLORA. 1 records from Naturalis Biodiversity Center (NL) - Chelicerata and Myriapoda. 74 records from Royal Belgian Institute of Natural Sciences Crustacea collection. 8 records from Inventaires floristiques des Grands Projets du Sud-Ouest (GPSO) 2010-2013. 24 records from The Nanoeukaryotic plankton Raw sequence reads. 452 records from Lake sediment sequencing. 1 records from Olga Lakela Herbarium, University of Minnesota Duluth. 662 records from The Taiwan Breeding Bird Survey Data. 30 records from Collection Crustacea - ZMB. 2 records from PERTH AVH data. 3150 records from Coral. 3 records from marine plankton metagenome Raw sequence reads. 11 records from Images of Flora and Fauna of 290 Leppitt Rd, Upper Beaconsfield. 587 records from REPHY - Réseau d'Observation et de Surveillance du Phytoplancton et de l'Hydrologie dans les eaux littorales. 48 records from ECT herbarium - Embrapa Clima Temperado - Herbário Virtual REFLORA. 228 records from New Mexico Museum of Natural History and Science (NMMNHS) Paleontology specimens (Arctos). 5 records from CDA - California Department of Food and Agriculture. 116 records from DNA metabarcoding assays reveal a diverse prey assemblage for Mobula rays in the Bohol Sea, Philippines. 1 records from 2018_nsmk_observations_bi. 2 records from Diversidad potencial de macroalgas en el Sistema de Información en Biodiversidad para Aysén (SIB-Aysén), Chile. 1 records from Marine Invertebrate voucher specimens at the Florida Biodiversity Collection, Florida Fish and Wildlife Conservation Commission. 22 records from Palaeontological collections National Museum of Natural History Luxembourg. 5 records from 2019_nsmk_biodiversity_observations_bi_10237. 5 records from Inventaire de la flore de Gironde 2017. 12 records from Distributions and Abundances of Sublineages of the N2-Fixing Cyanobacterium Candidatus Atelocyanobacterium thalassa (UCYN-A) in the Noumea Lagoon. 98 records from Bacteria in Anopheles darlingi breeding sites in Manaus, the Amazon, Brazil. 26 records from Quantitative monitoring of environmental DNA using high-throughput sequencing. 1 records from Lichen herbarium, UiT Tromsø Museum. 6 records from REAL herbarium - Universidade Federal da Fronteira Sul - Herbário Virtual REFLORA. 111 records from Methane and dissolved organic carbon fueled microbial loop supports a tropical subterranean estuary ecosystem. 19 records from Enrichment of organohalide respiring bacteria. 11 records from sediment metagenome Raw sequence reads. 103 records from Pelagic sediment metagenome of Gulf of Khambhat. 95 records from RON herbarium - Universidade Federal de Rondônia - Herbário Virtual REFLORA. 2 records from Manning & Great Lakes - NSW Waterwatch. 11 records from The Fungal Collection at the Senckenberg Museum für Naturkunde Görlitz. 3 records from RNF - Conservatoire d'espaces naturel Nord-Pas-de-Calais. 55 records from Peruvian eddy shotgun metagenomes. 2 records from Wikiplantbase Sicilia. 2 records from MBML Herbarium - Museu de Biologia Mello Leitão - Herbário Virtual Reflora. 14 records from Weed Population Genetics. 172 records from Sediment bacteria in the Southern Ocean. 6 records from Quantitative and Semi-quantitative survey of the vegetation of Seychelles through stand scale plots. 5 records from marine methane seep Targeted Locus (Loci). 1929 records from Victorian Biodiversity Atlas. 1 records from Museum of Southwestern Biology, Division of Arthropods. 97 records from Spatial and environmental variation in whole microbial communities in Fildes Bay, King George Island, Antarctica Raw sequence reads. Data from some individual datasets included in this download may be licensed under less restrictive terms.
Keywords: GBIF; biodiversity; species occurrences